THE RESPONSE OF CYLINDRICAL SANDWICH STRUCTURES INSPIRED BY BAMBOO UNDER UNIAXIAL COMPRESSIVE LOAD - Jihad Ummul Quro, M
Biomimetics is a branch of science that mimics structures or systems found in nature because structures that form in life are the most efficient. This efficient structure is copied and applied to human-made structures; so that the architecture created can be efficient and able to overcome more complex problems. One of the suitable plant structures is bamboo steams because the thickness of the bamboo bar is relatively thin compared to the diameter of the bamboo but can resist bending, twisting, and axial compressive loads. This structure like fuselage, so it is essential to study the characteristics of bamboo structures so that they can be the basis for designing aircraft fuselage structures. The anatomy of the bamboo structure has a vascular bundle. The reconstruction of the vascular bundle is using hexagonal shape and circle shape. Hexagonal shape and circle shape are made in a different coordinate. The hexagonal shape is made in a cartesian coordinate while circle shape is made in a cylindrical coordinate. The reconstruction model of bamboo structure tested with numerical simulation by Nastran software, and at the same time, the design printed by 3D printing. Then, the 3D printing model is tested with a static test. This experiment is essential to validate the result of numerical simulation. After that, the results of the static analysis are compared between 2 bamboo models (hexagonal and circle bamboo models) to get a better design. Based on the experimental, the maximum static compressive load that can be accepted by the reconstruction model of bamboo is 62246.6 N for the hexagonal model and 70917.7 N for the circle model. And by numerical simulation, it was gotten the result is 61344.1 N for the hexagonal model and 70192.5 N for the circle model. According to the experiment and simulation result, the different error of numerical simulation to the experiment test for the hexagonal model is 1.45%, and for the circle model is 1%. In addition, the specific load for the hexagonal model is 389041.9 N/kg, and for the circle mode is 393987.2 N/kg. So it was concluded that the circle model is better at holding compressive loads than the hexagonal model.